Inside Java 2 platform security : architecture, API design, and implementation - Gong, Li (Java series., 2003)
Series: The Java Series Security is an integral part of the Java platform; all Java APIs are built on a solid security model. That model has always been stronger than the security of other platforms, never allowing for the proliferation of a large virus such as "Melissa" or "I Love You." Now improved security and robust performance peacefully coexist. This book provides a detailed look into the central workings of the Java security architecture, including coverage of the many v1.4 enhancements. This book reviews multiple security threats, such as Trojan horses and denial of service attacks, and the strategies used to combat them. Students will find a practical guide to the deployment of Java security, as well as tips on how to customize, extend, and refine the core security architecture. In addition, it touches on the evolution of Java security, from the restrictive days of the JDK 1.0 sandbox to the sophisticated security features available in Java 2. The book even includes a list of 11 security bugs found in early versions of Java.